مشكلات تدريسيي ومحاضري المواد التربوية والنفسية والاجتماعية في الكليات الاختصاص في جامعة بغداد للعام الدراسي 2013/ 2014 من وجهة نظرهم وطلبتهم (Journal Of Educational and Psychological Researches, 2016)
Sought researcher to try to detect the type and size of the problems detected in or discovered or exposed or trying to find solutions to them as teachers and lecturers who are studying the educational, psychological and social articles in college studying these materials, whether the jurisdiction or extra materials, and clarified language definitions and terminology for search terms, indicating the importance of research into the problem of these either for teachers or for their students, and prepared a questionnaire organization questions open to get a clear responses and the Organization of the kind of problems faced by the lecturers and their students who are dealing with the educational, psychological and social articles in colleges jurisdiction at Baghdad University, and applied the questionnaire to a random sample of faculty and their students, and won very important for the type of problems, the results of these and counted researcher magnitude of the problems these loops and percentages as well as to clarify duties and graphics, then interpreted the results scientific explanation realistic and down to the recommendations and proposals very Mma seeking to minimize or reduce the problems this has the entire study population.